Madrasah Students' Difficulties in Geometry Material - Anil Muftirah; Jemmy Eko S.Putra; Nurhalisa; Irmayanti (COMPETITIVE: Journal of Education, 2023)
This study aims to identify the difficulties of class VIII students at MTS Negeri I Panreng Sinjai in studying mathematics in the subject of Geometry. In this research method. using a type of descriptive-qualitative method. The results of this study showed that students had difficulties in learning geometry material, namely students having difficulty in determining the volume of geometric figures, determining or calculating numbers with high numbers, students also had difficulty calculating using multiplication. That is because when learning mathematics subjects, especially geometry material, students do not understand geometry material, especially geometric shapes, in the atmosphere of the learning process the teacher conveys material that is less interesting and students also lack practice in working on math problems.